Stable light isotopes in fauna as environmental proxies in the Southern African winter and year-round rainfall zones - Luyt, Catherine (Department of Archaeology, 2017)
This study explores the effects of environmental and climatic variables on the stable carbon, nitrogen and oxygen isotopic values of wild African fauna from C3 dominated environments. Most previous studies of isotopic ecology in Africa have been carried out in summer rainfall regions. This study focuses on the winter rainfall zone in the southwestern part of Africa, where important archaeological sites record evidence of early modern humans. This study focuses on contemporary fauna to provide a baseline for the interpretation of stable isotope analyses of archaeological and fossil animals from this region, a key tool in the reconstruction of palaeoclimates and palaeoenvironments. It also contributes to a better understanding of isotope systematics in large mammals. δ¹³C and δ¹⁵N were measured in bone collagen, and δ¹³C and δ¹⁸O were measured in tooth enamel. Samples were taken from 27 species of indigenous wild mammals in game parks and nature reserves, i.e. relatively undisturbed natural environments. Animal species include primates, ungulates and carnivores collected from the following vegetation types: Savanna, Succulent Karoo, Nama Karoo, Fynbos, Afromontane Forest and Albany Thicket. Correlations between the isotopic measurements and meteorological factors were explored to assess the nature and strength of the relationships. Meteorological factors included mean annual precipitation (MAP), mean annual temperature (MAT), mean annual soil moisture stress (MASMS), mean annual potential evapotranspiration (MAPE), relative humidity (RH), summer aridity index (SAI), winter concentration of rainfall (WCR), moisture index (MI) and water deficit (WD).